2013
DOI: 10.1039/c3sm27735f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, swelling behavior, and viscoelastic properties of functional poly(hydroxyethyl methacrylate) with ureidopyrimidinone side-groups

Abstract: In this report the swelling and linear viscoelastic behavior of a hydrophilic polymer containing reversibly associating hydrogen bonding side-groups will be examined. Ureidopyrimidinone (UPy) moieties selfassociate to form hydrogen-bonded dimers (DDAA) in non-polar media; however, UPy behavior in water-swollen hydrogel environments is unclear. A series of technologically important, poly(hydroxyethyl methacrylate) (poly(HEMA)) polymers, with varying UPy side-group content, were prepared using a reversible addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 53 publications
(53 reference statements)
4
43
1
Order By: Relevance
“…These results are consistent with results for several other reported supramolecular polymers [63][64][65][66]. As discussed in the introduction, we predict that all our polymer samples are unentangled.…”
Section: A Linear Viscoelasticity and The Validity Of Ttssupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with results for several other reported supramolecular polymers [63][64][65][66]. As discussed in the introduction, we predict that all our polymer samples are unentangled.…”
Section: A Linear Viscoelasticity and The Validity Of Ttssupporting
confidence: 82%
“…Generally, it is thus important to understand the rheological response for a proper control of the material behaviour. The effect of UPy addition on the linear viscoelasticity of supramolecular polymers has previously been investigated [20,[63][64][65][66]. However, few studies exist where the rheological response is characterised for a systematic variation of supramolecular side-group density [41,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…The HEMA‐HEMA(UPy) copolymers of that study initially showed a very fast swelling rate. However, at longer swelling times, for the hydrogels containing more than 6 mol% HEMA(UPy) co‐monomer contents, the rate of swelling decreased but an equilibrium swelling was not reached within even several months …”
Section: Introductioncontrasting
confidence: 77%
“…For example, hydrogen bonding copolymers of UPyMA with n-butyl acrylate, 11,19 2-ethylhexyl methacrylate, 20 and 2-hydroxyethyl methacrylate 21 have been syn-3 thesized by making use of either free or controlled radical polymerization method. With thermally tunable strength of association, these hydrogen bonding copolymers display stimuli responsive rheological behavior, and may be employed as shape memory, selfhealing, and adhesive materials.…”
Section: Introductionmentioning
confidence: 99%